Peran Ekis dalam Mewujudkan Pembangunan Berkelanjutan Berbasis Green Ekonomi - Eka Yuni Hartati; Mulya Jayanti Putri; Mardhiyah Hayati (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Integration between Islamic economy and green economy in the context of sustainable development. In this modern era, environmental challenges are increasingly pressing, and a holistic approach is needed to overcome these problems. The concept of maqashid sharia, which includes the protection of religion, life, reason, property and descendants, provides a comprehensive framework for integrating social, economic and environmental aspects in development. Education and environmental awareness based on Islamic values ​​are one of the important pillars in creating a society that cares about the environment. Several mosques in Indonesia have implemented environmentally friendly principles by optimizing the use of renewable energy and managing waste effectively. This shows that religious institutions can play an active role in supporting the green economy. However, there are still many challenges faced in implementing a green economy in Indonesia, including a lack of environmental literacy in society and human exploitation of other humans. Therefore, this paper aims to find strategies and recommendations that can be implemented to integrate Islamic economics within a sustainable development framework, so as to create synergy between economic growth, social welfare and environmental preservation. Therefore, it is hoped that this paper can contribute to the moral and material development of Islamic society and encourage active participation in environmental conservation efforts. Criticism and suggestions from readers are highly welcomed for future improvements.